HUBUNGAN KOMUNIKASI ORGANISASI ANTAR PEGAWAI TERHADAP KINERJA PEGAWAI DINAS PARIWISATA KABUPATEN MAMASA - Marianus Marianus; Abd. Asis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
This study aims to determine the relationship of organizational communication, and to explain the process of employee performance, as well as communication barriers. The research is descriptive qualitative in nature to understand the phenomena that occur in the research subject with a phenomenological approach. Collecting data through observation, interviews, documentation study, literature study. The results showed that the organizational communication relationship between employees uses formal communication which is official model and can be done in groups or forums in the command line according to leadership communication. All employees cannot communicate directly to the leadership. The organizational communication relationship that occurs in the Mamasa Regency Tourism Office uses a top-down communication pattern and cross-channel communication. Some of the communication barriers are errors in the delivery of information from leaders to subordinates, semantic barriers, ambiguous barriers to communication between leaders and staff, physical barriers, and inability to convey information from the leadership to the staff.